Konseling Individu dalam Upaya Pemulihan Psikis Anak Korban Pedofilia Di Unit Pelaksana Teknis Daerah Perlindungan Perempuan dan Anak (UPTD PPA) Provinsi Lampung - Aisyah, Umi; Toharudin, Didin; Zuhdi, Muhammad Sholihuddin (Al Huwiyah: Journal of Woman and Children Studies, 2024)
AbstrackUntil now, many children have become victims of pedophilic sexual crimes. Pedophilia is defined as a sexual disorder in which adults have sexual attraction or fantasies towards children or pre-pubertal children. Victims of pedophilic abuse experience many problems, not only physical problems but also psychological problems. Psychologically, they experience anxiety disorders, trauma, loss of self-confidence, fear of meeting other people, and become closed individuals and they will even become pedophiles if not handled properly. For this reason, there must be various efforts to help psychologically recover children who are victims of pedophilia, one of which can be through individual counseling. Individual counseling is an assistance service provided by a counselor to a client directly or face to face with the aim of resolving problems experienced by the client by making the client aware and developing the client's personality so that the client can anticipate the problems being faced. This research is a qualitative research with data collection using observation and semi-structured interviews to determine the process of implementing individual counseling in efforts to psychologically recover children who are victims of pedophilia which is carried out at the UPTD PPA in Lampung province.Keyword: Individual Counseling, pedophilia, psychological recoveryAbstrakHingga saat ini banyak anak yang menjadi korban kejahatan seksual pedofilia. Pedofilia didefinisikan sebagai kelainan seksual di mana orang dewasa memiliki ketertarikan atau fantasi seksual terhadap anak-anak atau anak pra-pubertas. Korban pelecehan pedofilia mengalami banyak permasalahan tidak hanya masalah fisik tetapi juga masalah psikis. Secara psikis mereka mengalami gangguan kecemasan, trauma, hilangnya kepercayaan diri, takut bertemu orang lain, dan menjadi pribadi yang tertutup dan bahkan mereka akan mejadi pelaku pedofil apabila tidak ditangani dengan tepat. Untuk itu harus ada berbagai upaya untuk membantu memulihkan secara psikis anak korban pedofilia salah satunya dapat melalui konseling individu. Konseling individu merupakan layanan bantuan yang diberikan oleh konselor kepada seorang klien secara langsung atau bertatap muka dengan tujuan untuk menyelesaikan masalah yang dialami klien dengan cara menyadarkan dan mengembangkan pribadi klien agar klien dapat mengantisipasi permasalahan yang sedang dihadapi. Penelitian ini merupakan penelitian kualitatif dengan pengumpulan data menggunakan observasi dan wawancara semi terstruktur untuk mengetahui proses pelaksanaan konseling individu dalam upaya pemulihan psikis anak korban pedofilia yang dilakukan di UPTD PPA provinsi Lampung.Kata kunci: Konseling Individu, pemulihan psikis, pedofilia